THE DIGITAL GENDER DIVIDE: AN OVERVIEW - Marzano, Gilberto; Lubkina, Velta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
It has been observed that women, especially in developing countries, have significantly lower technology participation rates than men. This is generally considered to be the result of socio-cultural attitudes related to the expected role of women in society. The consequence is the low percentage of women working in the high-tech industry. However, nowadays, women make ample use of internet technology and access social media just as much as men.This article will explore the issue of the digital gender divide, focusing on which factors can impede and/or facilitate access to and use of digital technologies. It represents the preliminary results of an ongoing research conducted within a bilateral project entitled “Gender aspects of digital readiness and development of human capital” that involves the Latgalian region in Latvia and the Ternopil region in Ukraine, two regions that share similar socio-economic problems.The aim of the research is to increase the level of women’s inclusion in the labor market of the future, which itappears will be increasingly dominated by digital technologies. From this perspective, reducing the digital divide is crucial, but alternative forms of digital education will need to be introducedin order to facilitate the acquisition of digital competences.